2004
DOI: 10.1111/j.1439-0507.2004.01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype of Candida species associated with different conditions of vulvovaginal candidosis

Abstract: It is unknown whether strains isolated from recurrent vulvovaginal candidosis (RVVC), vulvovaginal candidosis (VVC) and asymptomatic carriers are varying or not in genotyping. Candida isolates were genotyped to determine whether specific types were associated with RVVC and VVC. A total of 97 Candida isolates from RVVC patients (n = 43), from VVC patients (n = 47) and asymptomatic carriers (n = 7) were identified by germ tube test, chlamydospore test, CHROMagar Candida and API20 system and were genotyped by pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 18 publications
3
10
2
Order By: Relevance
“…The present study implies that the strains with the dominant genotypes are more virulent than others in causing VVC, and that strain differences may play a significant role in the aetiology of VVC. These observations are inconsistent with those of previous studies 11 12 19…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present study implies that the strains with the dominant genotypes are more virulent than others in causing VVC, and that strain differences may play a significant role in the aetiology of VVC. These observations are inconsistent with those of previous studies 11 12 19…”
Section: Discussioncontrasting
confidence: 99%
“…It is unknown whether genotypes of C albicans strains correlate with severity or other conditions of VVC. Genotyping of vaginal C albicans isolates based on randomly amplified polymorphic DNA (RAPD) analysis failed to show the obvious relatedness of genotypes with VVC and recurrent VVC patient groups 11 12. The severity of infection was not, however, considered in those studies.…”
mentioning
confidence: 99%
“…Different genotyping methods may result in different groupings of isolates. For example, inconsistent with our observations based on CAI polymorphism (8,11), genotyping of vaginal C. albicans isolates by using randomly amplified polymorphic DNA (RAPD) analysis failed to show any relationship between genotypes and VVC patient groups (3,12). Another possible reason is that the genotype distribution patterns of VVC causing C. albicans isolates in Chinese and European women may be different.…”
Section: Discussioncontrasting
confidence: 52%
“…Different genotypes of all the isolates and lack of differences between diabetic and control groups also indicate that host-related factors are predominantly involved in the pathogenesis of the widely prevalent Candida infection among patients with DM. In a study by Lian et al 15 on VVC in nondiabetic women, it was concluded that the AP-PCR amplification products were similar among isolates from different individuals. In India, there appears to be a higher glycosylated hemoglobin (HbA1) level in patients with DM and VVC as compared with diabetics without VVC (12.8 AE 2.6% vs. 9.7 AE 1.7%, respectively; p Z 0.001).…”
Section: Discussionmentioning
confidence: 96%